Pest categorisation of Elsinoë fawcettii and E. australis. (20th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Grégoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of Elsinoë fawcettii and E. australis, the causal agents of citrus scab diseases, for the EU. The identities of the pests are well‐established and reliable methods exist for their detection/identification. The pests are listed in Annex IIAI of Directive 2000/29/EC as Elsinoë spp. and are not known to occur in the EU. Species and hybrids of citrus (Family Rutaceae) are affected by E. fawcettii and E. australis, with the latter having a more restricted host range and geographical distribution compared to the former. The status of Simmondsia chinensis (jojoba) as a host of E. australis is uncertain. The pests could potentially enter the EU on host plants for planting and fruit originating in infested Third countries. The current distribution of the pests, climate matching and the use of irrigation in the EU citrus‐growing areas suggest that the pests could establish and spread in the EU citrus‐growing areas. Uncertainty exists on whether cultural practices and control methods, currently applied in the EU, would prevent the establishment of the pests. In the infested areas, the pests cause scab pustules on host leaves and fruit resulting in yield/quality losses. It is expected that the introduction and spread of the pests in the EU could impact citrus production. Cultural practices and chemical control measures may reduce the inoculum sources and to some extent the disease incidence, but they cannot eliminate the pests. Phytosanitary measures are available to mitigate the risk of introduction and spread of the pests in the EU. E. fawcettii and E. australis meet all the criteria assessed by EFSA for consideration as potential Union quarantine pests. As those pests are not known to occur in the EU, this criterion to consider them as Union regulated non‐quarantine pests is not met.